PRODUCTIVE PERFORMANCES OF COMMERCIAL BROILER CHICKEN UNDER INTERMITTENT LIGHT AND COLOURED LIGHT REGIME (Indian Journal of Animal Production and Management, 2014)
A total of 200 broiler chicks of Vencob-100 strain were procured and reared under standard management conditions till 42 days of experiment. After completion of one week they were divided into 8 groups according to different light regime mixing colour of light and intermittent light. The values for body weight (gm) at the end of 4th week of age under blue and green coloured light having light duration 20 L + 4D was differ significantly (P
Keywords: Broiler Chicken; Coloured light; Growth Performance